Near-zero-wear polymer-based ionic liquid as well as preparation method and application thereof
By preparing polymer-based ionic liquids, the problems of insufficient wear and corrosion resistance of existing liquid lubricants under high load conditions have been solved, achieving ultra-low wear and excellent lubrication performance on steel substrates, making it suitable for a variety of complex mechanical equipment.
Patent Information
- Application Number
- CN202511010047.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-11-07
AI Technical Summary
Existing liquid lubricants are difficult to achieve ultra-low wear under high load conditions and lack sufficient corrosion resistance, thus failing to meet the tribological requirements of complex mechanical equipment.
A polymer-based ionic liquid, specifically composed of polyethyleneimine cations and phosphate anions, is prepared through a proton exchange reaction to produce a polymer-based ionic liquid with high viscosity and excellent wettability for use in the lubrication of steel substrates.
It significantly reduces the coefficient of friction under high loads and complex environments, achieving ultra-low wear of steel friction pairs, and exhibits good corrosion resistance and high viscosity, making it suitable for a variety of harsh conditions.
Smart Images

Figure CN120904450A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of friction lubrication, in particular to a near-zero wear polymer-based ionic liquid and a preparation method and application thereof. BACKGROUND
[0002] Mechanical components will wear during operation, which seriously affects the safety and reliability of equipment use, causes low energy efficiency and economic losses. The reasonable application and innovation of lubricating materials provide a feasible solution to this tribology problem. Among them, liquid lubricants have the effects of cleaning, cooling, fire resistance, friction control and wear reduction in mechanical and engineering applications, and become one of the most cost-effective and most common solutions. However, the traditional liquid lubricants have the disadvantages of high corrosiveness, poor temperature resistance, easy leakage and the like. In addition, the limited tribological performance of the existing liquid lubricants gradually cannot meet the harsh operating conditions. At present, most liquid lubricants are still striving to achieve ultra-low wear performance, and the research results mainly focus on achieving ultra-low wear under specific conditions or at a microscale, and only provide limited anti-wear protection for specific friction pairs. It is still a challenge to achieve ultra-low wear on the surface of engineering steel under various conditions of mechanical equipment operation.
[0003] Ionic liquids have attracted extensive attention in the field of tribology since they were first studied as lubricants in 2001. Ionic liquids form stable lubricating films on various metal surfaces through electrostatic interaction, van der Waals force and hydrogen bonding, thereby reducing friction and severe wear.
[0004] The prior art discloses an ionic liquid taking a fatty amine as a cation and a phosphate as an anion as a lubricant, but the above ionic liquid used for lubrication is only suitable for low-load working conditions. SUMMARY
[0005] Therefore, the present application aims to provide a polymer-based ionic liquid and a preparation method and application thereof. The polymer-based ionic liquid provided by the present application still has ultra-low wear behavior under high-load working conditions.
[0006] In order to achieve the above-mentioned application purposes, the present application provides the following technical solutions:
[0007] The present application provides a polymer-based ionic liquid, which comprises a polyethyleneimine cation and a phosphate anion.
[0008] Preferably, the phosphate anion is a dibutyl phosphate anion or a di(2-ethylhexyl) phosphate anion.
[0009] Preferably, the relative molecular mass of the polyethyleneimine cation is 600-10000.
[0010] Preferably, the mole percentage of the polyethylene imine cation in the total mole of the polyethylene imine cation and the phosphate ester anion is 5-20%.
[0011] Preferably, the viscosity coefficient of the polymer-based ionic liquid is 3-13 Pa·s.
[0012] The application also provides a preparation method of the polymer-based ionic liquid.
[0013] The polyethylene imine and the phosphate ester are mixed to perform a proton exchange reaction to obtain the polymer-based ionic liquid.
[0014] Preferably, the medium of the proton exchange reaction is an alcohol solvent.
[0015] After the proton exchange reaction, the medium of the proton exchange reaction is removed.
[0016] Preferably, the mole percentage of the polyethylene imine in the total mole of the polyethylene imine and the phosphate ester is 5-20%.
[0017] Preferably, the proton exchange reaction is performed under stirring, the stirring speed is 300-800 rpm, and the time is 8-12 h.
[0018] The application also provides an application of the polymer-based ionic liquid or the polymer-based ionic liquid prepared by the preparation method in the field of friction lubrication.
[0019] The application provides a polymer-based ionic liquid.
[0020] The polymer-based ionic liquid provided by the application takes the polyethylene imine cation rich in active nitrogen elements as the cation and takes the phosphate ester anion as the anion. The polymer-based ionic liquid has good thermal stability and wettability to a steel matrix, high viscosity and adhesion, a suitable pH value, and excellent corrosion resistance. Compared with traditional lubricants, the polymer-based ionic liquid can significantly reduce the friction coefficient, significantly reduce the wear of a steel friction pair surface, and realize long-term ultra-low wear on the steel contact surface under high load and complex application environments, and has excellent tribological properties.
[0021] The data of the embodiments show that the polymer-based ionic liquid of the present application is applied to a steel / steel friction pair, and the average friction coefficient is 0.082-0.105 under the condition of 100N (the Hertz contact pressure is 2.15GPa) and 30min, and there is no obvious wear trace on the surface of the friction pair. Even during the friction experiment for 150min, the average friction coefficient of the polymer-based ionic liquid is 0.076, and the wear rate is only 1.46*10 -10 mm 3 ·N -1 ·m -1 ; meanwhile, the polymer-based ionic liquid lubricant provided by the present application is applied to a steel / steel friction pair under different temperature (30-90℃) and frequency (25-45Hz) conditions, and the polymer-based ionic liquid exhibits excellent friction reduction performance; and through the copper corrosion experiment, it is proved that the corrosion degree of the copper sheet by the polymer-based ionic liquid lubricant provided by the present application is lighter, which shows that the polymer-based ionic liquid has excellent corrosion resistance. In summary, the polymer-based ionic liquid of the present application can realize low friction coefficient and ultra-low wear performance when applied to a steel surface, and has strong bearing capacity, good corrosion resistance, and wide application prospect.
[0022] The present application also provides a preparation method of the polymer-based ionic liquid described in the above technical solution, and the preparation method provided by the present application is simple to operate and economical and environmentally friendly in process. BRIEF DESCRIPTION OF DRAWINGS
[0023] Figure 1 The polymer-based ionic liquid prepared in Example 1 is applied to a steel / steel friction pair, and the friction curve graph and wear trace light microscope graph obtained by testing under the condition of 100N, 30min are shown in the following figure;
[0024] Figure 2 The polymer-based ionic liquid prepared in Example 2 is applied to a steel / steel friction pair, and the friction curve graph and wear trace light microscope graph obtained by testing under the condition of 100N, 30min are shown in the following figure;
[0025] Figure 3 The polymer-based ionic liquid prepared in Example 3 is applied to a steel / steel friction pair, and the friction curve graph and wear trace light microscope graph obtained by testing under the condition of 100N, 30min are shown in the following figure;
[0026] Figure 4 The polymer-based ionic liquid prepared in Example 4 is applied to a steel / steel friction pair, and the friction curve graph and wear trace light microscope graph obtained by testing under the condition of 100N, 30min are shown in the following figure;
[0027] Figure 5 The polymer-based ionic liquid prepared in Example 2 is applied to a steel / steel friction pair, and the friction curve graph and wear trace light microscope graph obtained by testing under the condition of 100N, 150min are shown in the following figure;
[0028] Figure 6 Figure 2 is a graph showing the change in the polished copper surface after exposure to various media at 55°C for 8h;
[0029] Figure 7 Figure 3 is an optical photograph of the polymer-based ionic liquid prepared in Example 1-4;
[0030] Figure 8 Figure 4 is an infrared spectrum of the polymer-based ionic liquid prepared in Example 1-4. DETAILED DESCRIPTION
[0031] The present application provides a polymer-based ionic liquid, comprising a polyethyleneimine cation and a phosphate anion.
[0032] The polymer-based ionic liquid provided by the present application comprises a polyethyleneimine cation, which is formed by protonation of a polyethyleneimine. In the present application, the relative molecular mass of the polyethyleneimine cation is preferably 600-10000, specifically 600, 800, 1000, 1800, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000 or 10000. In the present application, the polyethyleneimine cation is formed by protonation of the amino group on the polyethyleneimine.
[0033] The polymer-based ionic liquid provided by the present application comprises a phosphate anion, which is preferably a dibutyl phosphate anion or a di(2-ethylhexyl) phosphate anion. In the present application, the phosphate anion is formed by deprotonation of a phosphate ester.
[0034] In the present application, the molar amount of the polyethyleneimine cation in the polymer-based ionic liquid preferably accounts for 5-20%, further preferably 10-18%, specifically preferably 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20% of the total molar amount of the polyethyleneimine cation and the phosphate anion.
[0035] In the present application, the polymer-based ionic liquid is preferably a homogeneous transparent viscous liquid, which behaves as a Newtonian fluid at room temperature (25℃). In the present application, the viscosity coefficient of the polymer-based ionic liquid is preferably 3-13 Pa·s, and more preferably 3 Pa·s, 4 Pa·s, 5 Pa·s, 6 Pa·s, 7 Pa·s, 8 Pa·s, 9 Pa·s, 10 Pa·s, 11 Pa·s, 12 Pa·s or 13 Pa·s. In the present application, the viscosity coefficient of the polymer-based ionic liquid is preferably measured under normal temperature and pressure. In the present application, the polymer-based ionic liquid exhibits excellent wettability and corrosion resistance on the surface of a metal substrate. In the present application, the contact angle of the polymer-based ionic liquid on the metal substrate is preferably 29-40°, and more preferably 29°, 30°, 30.5°, 31°, 32°, 32.8°, 33°, 33.6°, 34°, 35°, 36°, 37°, 38°, 39°, 39.8° or 40°.
[0036] In the present application, the polymer-based ionic liquid is a high-molecular derivative of a macroscopically electrically neutral ionic liquid.
[0037] The polymer-based ionic liquid provided by the present application has excellent tribological properties on the surface of a metal substrate, specifically embodied in the following aspects: (1) strong load-carrying capacity, excellent friction-reducing and wear-resistant properties under high load of 100 N (Hertz contact pressure of 2.15 GPa); (2) good lubricating properties during long-time (150 min) friction test under high load of 100 N (Hertz contact pressure of 2.15 GPa); (3) good lubricating properties under high test frequency (45 Hz); (4) excellent friction-reducing and wear-resistant properties under high temperature (90℃); (5) excellent friction-reducing and wear-resistant properties after long-time storage (120 days); (6) good corrosion resistance, with little obvious corrosion on copper sheets. In summary, the polymer-based ionic liquid of the present application has excellent tribological properties, can achieve ultra-low wear behavior on the surface of a metal substrate under complex environment, has strong load-carrying capacity and good corrosion resistance, which is of great significance for the research and application of liquid lubricants in the field of tribology, and has a broad application prospect in the field of friction and lubrication.
[0038] The present application also provides a preparation method of the polymer-based ionic liquid described in the above technical solution, which comprises the following steps:
[0039] The polyethyleneimine and the phosphate ester are mixed and subjected to proton exchange reaction to obtain the polymer-based ionic liquid.
[0040] In the present application, the mole percentage of the polyethyleneimine in the total moles of the polyethyleneimine and the phosphate is preferably 5-20%, further preferably 10-18%, and particularly preferably 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or 20%.
[0041] In the present application, the medium for the proton exchange reaction is preferably an alcohol solvent, further preferably ethanol, and more preferably anhydrous ethanol. The amount of the medium for the proton exchange reaction is not particularly limited in the present application, as long as the polyethyleneimine and the phosphate can be mixed sufficiently.
[0042] In the present application, the temperature for the proton exchange reaction is preferably room temperature, i.e., no additional heating or cooling is required. In the present application, the proton exchange reaction is preferably carried out under stirring, and the stirring speed is preferably 300-800 rpm, and particularly preferably 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, or 800 rpm. The time is preferably 8-12 h, and particularly preferably 8 h, 9 h, 10 h, 11 h, or 12 h. In the present application, the proton exchange reaction is preferably carried out under sealing. In the present application, the proton exchange reaction is carried out under sealing, which can avoid the influence of evaporated solvent on the product.
[0043] After the proton exchange reaction, the present application preferably further comprises removing the medium for the proton exchange reaction. The method for removing the medium for the proton exchange reaction is preferably rotary evaporation, and the temperature for the rotary evaporation is preferably 70°C. The time for the rotary evaporation is not particularly limited in the present application, as long as the medium for the proton exchange reaction can be removed completely.
[0044] After removing the medium for the proton exchange reaction, the present application preferably further comprises drying. The temperature for the drying is preferably 60-80°C, and particularly preferably 60°C, 65°C, 70°C, 75°C, or 80°C. The time is preferably 12-24 h, and particularly preferably 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, or 24 h. The vacuum degree is preferably 10-133 Pa, and particularly preferably 10 Pa, 20 Pa, 30 Pa, 40 Pa, 50 Pa, 60 Pa, 70 Pa, 80 Pa, 90 Pa, 100 Pa, 110 Pa, 120 Pa, 130 Pa, or 133 Pa. In the present application, the drying is preferably carried out in a vacuum drying oven.
[0045] In the present application, the polyethyleneimine and the phosphate are subjected to a proton exchange reaction to form a polymer-based ionic liquid having polyethyleneimine cations and phosphate anions.
[0046] The preparation method is simple, easy to operate, low in cost, and has wide application prospect.
[0047] The application also provides application of the polymer-based ionic liquid or the polymer-based ionic liquid prepared by the preparation method in the field of lubrication.
[0048] The application mode of the polymer-based ionic liquid is not specifically limited, and a person skilled in the art can set it according to actual needs.
[0049] The polymer-based ionic liquid, the preparation method and the application thereof provided by the application will be described in detail below in combination with examples, but they should not be understood as limitations to the protection scope of the application.
[0050] Example 1
[0051] A polymer-based ionic liquid, and the preparation steps are as follows:
[0052] 0.54g of polyethyleneimine (Mw=600, 0.9mmol) and 1.07g of di(2-ethylhexyl) phosphate (209.2004, 5.11mmol) are weighed and added into a 100mL beaker containing 20mL of anhydrous ethanol, a magnetic stirrer is placed and sealed with a sealing film.
[0053] The anhydrous ethanol solution containing polyethyleneimine and di(2-ethylhexyl) phosphate is magnetically stirred at 500rpm for 10h at room temperature to obtain a yellow or colorless transparent solution.
[0054] The obtained yellow or colorless solution is transferred into a 100mL single-necked flask, the solvent is removed by rotary evaporation at 70℃, and the obtained polymer-based ionic liquid is dried in a vacuum drying box at 100Pa and 70℃ for 24h and recorded as PEI 0.6K EPA, the viscosity coefficient of the obtained polymer-based ionic liquid at normal temperature and pressure is determined by a rotary rheometer, and the result is 3Pa·s; the contact angle on a metal substrate is 30.5°.
[0055] Example 2
[0056] A polymer-based ionic liquid, and the preparation steps are as follows:
[0057] 2.72g of polyethyleneimine (Mw=1800, 1.51mmol) and 1.79g of di(2-ethylhexyl) phosphate (209.2004, 8.56mmol) are weighed and added into a 100mL beaker containing 20mL of anhydrous ethanol, a magnetic stirrer is placed and sealed with a sealing film.
[0058] The solution of polyethyleneimine and di(2-ethylhexyl) phosphate in anhydrous ethanol was magnetically stirred at 500 rpm for 10 h at room temperature to obtain a yellow or colorless transparent solution.
[0059] The obtained yellow or colorless solution was transferred into a 100 mL single-necked flask, and the solvent was removed by rotary evaporation at 70 °C, and then dried in a vacuum drying box at 100 Pa and 70 °C for 24 h to obtain a polymer-based ionic liquid, denoted as PEI 1.8K EPA, the viscosity coefficient of the obtained polymer-based ionic liquid at normal temperature and pressure was determined by a rotary rheometer, and the result was 4 Pa·s; the contact angle on a metal substrate was 33.6°.
[0060] Example 3
[0061] A polymer-based ionic liquid was prepared by the following steps:
[0062] 1.75 g of polyethyleneimine (Mw = 1800, 0.97 mmol) and 1.16 g of dibutyl phosphate (209.2004, 5.54 mmol) were weighed and added to a 100 mL beaker containing 20 mL of anhydrous ethanol, and a magnetic stirrer was placed and sealed with a sealing film.
[0063] The solution of polyethyleneimine and di(2-ethylhexyl) phosphate in anhydrous ethanol was magnetically stirred at 500 rpm for 10 h at room temperature to obtain a yellow or colorless transparent solution.
[0064] The obtained yellow or colorless solution was transferred into a 100 mL single-necked flask, and the solvent was removed by rotary evaporation at 70 °C, and then dried in a vacuum drying box at 100 Pa and 70 °C for 24 h to obtain a polymer-based ionic liquid, denoted as PEI 1.8K DPA, the viscosity coefficient of the obtained polymer-based ionic liquid at normal temperature and pressure was determined by a rotary rheometer, and the result was 4 Pa·s; the contact angle on a metal substrate was 33.6°.
[0065] Example 4
[0066] A polymer-based ionic liquid was prepared by the following steps:
[0067] 5.4 g of polyethyleneimine (Mw = 10000, 0.54 mmol) and 0.64 g of di(2-ethylhexyl) phosphate (209.2004, 3.06 mmol) were weighed and added to a 100 mL beaker containing 20 mL of anhydrous ethanol, and a magnetic stirrer was placed and sealed with a sealing film.
[0068] The solution of polyethyleneimine and di(2-ethylhexyl) phosphate in anhydrous ethanol was magnetically stirred at 500 rpm for 10 h at room temperature to obtain a yellow or colorless transparent solution.
[0069] The obtained yellow or colorless solution was transferred into a 100 mL single-necked flask, the solvent was removed by rotary evaporation at 70°C, and the polymer-based ionic liquid was obtained by drying in a vacuum drying box at 100 Pa and 70°C for 24 h, and was denoted as PEI 10K EPA, the viscosity coefficient of the obtained polymer-based ionic liquid was determined by a rotary rheometer at room temperature and normal pressure, and the result was 12 Pa·s; the contact angle on a metal substrate was 39.8°.
[0070] Comparative Example 1
[0071] In order to more fully describe the tribological properties of the polymer-based ionic liquid on a steel contact surface, a conventional polar base oil, polyethylene glycol (PEG400), was used as a reference sample for tribological testing, so as to better illustrate the low friction and near-zero wear properties of the polymer-based ionic liquid on a steel contact surface. The SRV-V friction tester was used to test the tribological properties of PEG400, and the test conditions were the same as in Examples 1-4. The results are shown in Table 1.
[0072] Comparative Example 2
[0073] In order to more fully describe the tribological properties of the polymer-based ionic liquid on a steel contact surface, a commercially available lubricating oil 5W30 was used as a reference sample for tribological testing, so as to better illustrate the low friction and near-zero wear properties of the polymer-based ionic liquid on a steel contact surface. The SRV-V friction tester was used to test the tribological properties of PEG400, and the test conditions were the same as in Examples 1-4. The results are shown in Table 1.
[0074] Comparative Example 3
[0075] The difference from Example 2 is that 1.51 mmol of polyethyleneimine (Mw = 1800) was replaced by 1.51 mmol of octadecylamine, and the other conditions were the same as in Example 2.
[0076] Comparative Example 4
[0077] The difference from Example 2 is that 1.51 mmol of polyethyleneimine (Mw = 1800) was replaced by 1.51 mmol of diethylamine, and the other conditions were the same as in Example 2.
[0078] Test 1
[0079] The SRV-V friction tester was used to test the tribological properties of the polymer-based ionic liquid obtained in Examples 1-4, and the reciprocating mode was used during the test. Steel balls (AISI52100, HRC = 60 ± 2, D = 10 mm) were used as the upper friction pair, and cylindrical steel discs (AISI52100, HRC = 60 ± 2, 24 mm x 7.9 mm) were used as the lower friction pair; the upper and lower friction pairs were cleaned with anhydrous ethanol before and after the test, and were then dried and installed on the friction tester; the PEI 0.6K EPA was applied to the lower friction pair cylindrical steel disc, and the tribological test was performed; the test conditions were: load 100 N (Hertz contact pressure 2.15 GPa), stroke 1 mm, frequency 25 Hz, time 30 min, and temperature 30°C; the friction coefficient curve and wear scar width were recorded. The results are shown in Figures 1 to 4 and Table 1.
[0080] Figure 1 The polymer-based ionic liquid prepared in Example 1 was applied to a steel / steel friction pair, and the friction curve and optical microscope image of the wear trace were tested under 100 N, 30 min; from Figure 1 It can be seen that the PEI 0.6K EPA has excellent friction reduction and wear resistance, with an average friction coefficient of 0.105 and no obvious wear trace on the steel substrate, showing significant ultra-low wear behavior.
[0081] Figure 2 The polymer-based ionic liquid prepared in Example 2 was applied to a steel / steel friction pair, and the friction curve and optical microscope image of the wear trace were tested under 100 N, 30 min; from Figure 2 It can be seen that the PEI 1.8K EPA has excellent tribological properties, with an average friction coefficient further reduced to 0.082, and the steel substrate still has no obvious wear trace, showing significant ultra-low wear behavior.
[0082] Figure 3 The polymer-based ionic liquid prepared in Example 3 was applied to a steel / steel friction pair, and the friction curve and optical microscope image of the wear trace were tested under 100 N, 30 min; from Figure 3 It can be seen that the PEI 1.8K DPA has good tribological properties, with an average friction coefficient of 0.101 and only shallow scratches on the steel substrate, with a wear scar diameter of 227 μm.
[0083] Figure 4 The polymer-based ionic liquid prepared in Example 4 was applied to a steel / steel friction pair, and the friction curve and optical microscope image of the wear trace were tested under 100 N, 30 min; fromFigure 4 It can be seen that the PEI obtained in Example 4 has a lower average friction coefficient than the PEI obtained in Example 1. 10K The EPA has good tribological properties, with an average friction coefficient of 0.095. Although the wear trace on the surface of the steel substrate is deepened, the EPA still exhibits excellent wear resistance, with a wear scar diameter of 295 μm.
[0084] Table 1 Comparison of tribological properties of lubricants obtained in Examples and Comparative Examples
[0085] Item Lubricant Average coefficient of friction Abrasion diameter (pm) Wear rate / mm 3 • N -1 • m -1 ]]> Example 1 PEI 0.6K EPA 0.105 - 7.39E-10 Example 2 PEI 1.8K EPA 0.082 - 3.27E-10 Example 3 PEI 1.8K DPA 0.101 227 8.11E-10 Example 4 PEI 10K EPA 0.095 295 1.11E-9 Comparative Example 1 PEG 400 0.125 513 1.18E-7 Comparative Example 2 5W30 0.116 304 4.43E-9 Comparative Example 3 0.107 297 3.14E-9 Comparative Example 4 0.113 311 7.82E-9
[0086] As shown in Table 1, the PEI prepared in Examples 1 to 4 has a lower average friction coefficient than the PEI prepared in Example 1. 0.6K EPA, PEI 1.8K EPA, PEI 1.8K DPA and PEI 10K The average friction coefficients of the EPA in the 30 min friction and wear test are 0.105, 0.082, 0.101 and 0.095, respectively. The surface of the steel substrate is almost not worn. Compared with the average friction coefficients of the conventional polyethylene glycol (PEG400) lubricating oil and the commercially available oil (5W30) used in the Comparative Example, which are 0.125 and 0.116, respectively, and the wear scar diameters are 513 μm and 304 μm, respectively, the average friction coefficient is obviously reduced, and the wear of the steel substrate is significantly reduced, which further indicates that the polymer-based ionic liquid prepared in Examples 1 to 4 has excellent tribological properties.
[0087] Test Two
[0088] The difference from Test One is that the time is extended to 150 min, and the sample is only the polymer-based ionic liquid obtained in Example 2. The results are shown in Table 2. Figure 5 Figure 5 The polymer-based ionic liquid prepared in Example 2 is applied to a steel / steel friction pair, and the friction curve and the wear trace light microscope graph obtained by testing under 100 N and 150 min are shown in Figure 2. Figure 5 It can be seen that the average friction coefficient is 0.076, and the wear scar diameter of the steel disc is 206 μm.
[0089] Test Three
[0090] The average friction coefficients of the polymer-based ionic liquid obtained in Example 2 at different temperatures are studied, and the method is the same as that of Test One. The test conditions are: load 100 N, stroke 1 mm, frequency 25 Hz, time 30 min, and only the temperature is adjusted to 30°C, 45°C, 60°C, 75°C and 90°C, respectively. The results are shown in Table 2.
[0091] Table 2 Average friction coefficients of the polymer-based ionic liquid obtained in Example 2 at different temperatures
[0092] Lubricant (PEI 1.8K EPA) 30℃ 45℃ 60℃ 75℃ 90℃ Average coefficient of friction 0.082 0.083 0.085 0.083 0.101
[0093] As can be seen from Table 2, the average friction coefficient of PEI 1.8K The average friction coefficient of EPA remained at a low level (0.082-0.085) with little fluctuation, indicating that the lubricant was stable in performance in this temperature range. When the temperature rose to 90°C, the average friction coefficient increased to 0.101, but was still at a low level, indicating that PEI 1.8K EPA has excellent lubricating performance.
[0094] Test four
[0095] The average friction coefficient of the polymer-based ionic liquid obtained in Research Example 2 at different frequencies was tested according to Test One, with the test conditions being: load 100 N, stroke 1 mm, time 30 min, temperature 30°C, and only the frequency being adjusted to 25 Hz, 30 Hz, 35 Hz, 40 Hz and 45 Hz, respectively. The results are shown in Table 3.
[0096] Table 3 Average friction coefficient of the polymer-based ionic liquid obtained in Research Example 2 at different frequencies
[0097] Lubricant (PEI 1.8K EPA) 25 Hz 30 Hz 35 Hz 40 Hz 45 Hz Average coefficient of friction 0.082 0.088 0.086 0.087 0.092
[0098] As can be seen from Table 3, within the test frequency range (25-45 Hz), the average friction coefficient of PEI 1.8K EPA has a low average friction coefficient. As the frequency increases, the average friction coefficient shows a small fluctuation, but does not show a clear monotonic upward or downward trend. Even when the test frequency reaches 45 Hz, the average friction coefficient is only 0.092, showing excellent tribological performance.
[0099] Test five
[0100] After the polymer-based ionic liquid obtained in Example 2 was stored at room temperature for 7 days, 30 days and 120 days, the average friction coefficient was tested according to Test One, with the test conditions being: load 100 N, stroke 1 mm, time 30 min, temperature 30°C. The results are shown in Table 4.
[0101] Table 4 Average friction coefficient of the polymer-based ionic liquid obtained in Example 2 after storage for 7, 30 and 120 days
[0102] Lubricant (PEI 1.8K EPA) Fresh 7 days 30 days 120 days Average coefficient of friction 0.082 0.085 0.089 0.090
[0103] As can be seen from Table 4, even after 120 days of storage, the average friction coefficient remained at a low level (0.090), only increased by about 9.8% compared with the initial value, indicating that PEI 1.8K EPA has long-term effective lubricating performance.
[0104] Test six
[0105] Copper corrosion tests were performed on the polymer-based ionic liquids obtained in Examples 1-4 according to GB / T 6144-2010 standard, and the results are shown in Figure 6 . Figure 6 The changes in the polished copper surface after 8h exposure to various media at 55°C. From Figure 6 it can be seen that: the copper immersed in the blank (mass ratio of ethanol / water = 1 / 1) solution, the surface color of the copper has undergone significant changes; this indicates that the medium (blank solution) has obvious corrosion effect. In contrast, after the introduction of 1wt% polymer-based ionic liquid, no obvious corrosion signs were observed on the copper surface. These findings highlight the excellent corrosion protection performance of the polymer-based ionic liquid.
[0106] Figure 7 Optical photographs of the polymer-based ionic liquids prepared in Examples 1-4, from Figure 7 it can be seen that the polymer-based ionic liquids prepared in Examples 1-4 are colorless or yellow transparent liquid, without turbidity and delamination phenomenon.
[0107] Figure 8 Infrared spectra of the polymer-based ionic liquids prepared in Examples 1-4; from Figure 8 it can be seen that the polymer-based ionic liquids prepared have peaks at 3200-3400cm -1 and 1000-1200cm -1 , which correspond to N + -H stretching vibration and C-N bending vibration, respectively. The characteristic peaks at 2825-2935cm -1 are C-H stretching vibration, and the characteristic peaks at 1220cm -1 and 1053cm -1 are the presence of P=O and P-O in the polymer-based ionic liquid. The above results prove the successful synthesis of the polymer-based ionic liquid.
[0108] The above only describes the preferred embodiments of the present application, it should be noted that for those skilled in the art, without departing from the principles of the present application, can make several improvements and refinements, these improvements and refinements should also be considered as the protection scope of the present application.
Claims
1. A polymer-based ionic liquid, comprising polyethyleneimine cation and phosphate anion.
2. The polymer-based ionic liquid of claim 1, wherein, The phosphate anion is dibutyl phosphate anion or di(2-ethylhexyl) phosphate anion.
3. The polymer-based ionic liquid of claim 1, wherein, The relative molecular mass of the polyethyleneimine cation is 600-10000.
4. The polymer-based ionic liquid according to claim 1 or 3, characterized in that, The mole percentage of the polyethyleneimine cation in the polymer-based ionic liquid is 5-20% of the total mole percentage of the polyethyleneimine cation and the phosphate anion.
5. The polymer-based ionic liquid of claim 1, wherein, The viscosity coefficient of the polymer-based ionic liquid is 3-13 Pa·s.
6. The method of claim 1 to 5, wherein the polymer-based ionic liquid is prepared by the reaction of a polymerizable ionic liquid and a polymerizable monomer. The method comprises the following steps: mixing polyethyleneimine and phosphate to perform proton exchange reaction to obtain the polymer-based ionic liquid.
7. The production method according to claim 6, wherein The medium of the proton exchange reaction is alcohol solvent. After the proton exchange reaction, the medium of the proton exchange reaction is removed.
8. The preparation method according to claim 6, characterized in that, The mole percentage of the polyethyleneimine is 5-20% of the total mole percentage of the polyethyleneimine and the phosphate.
9. The preparation method according to claim 6, characterized in that, The proton exchange reaction is performed under stirring, the stirring speed is 300-800 rpm, and the time is 8-12 h.
10. Use of the polymer-based ionic liquid of any one of claims 1-5 or the polymer-based ionic liquid prepared by the method of any one of claims 6-9 in the field of friction lubrication.